Mapping producer services networks in mainland Chinese cities. (December 2015) - Zhao, Miaoxi; Liu, Xingjian; Derudder, Ben; Zhong, Ye; Shen, Wei
We analyse the geographies of urban networks created by leading producer services (PS) firms in China. Because of the national regulation of the Chinese state-led economy and the location strategies of global advanced producer services (APS) firms, the geography of global APS in China as examined by the Globalization and World Cities Research Network (GaWC) cannot be studied as a subnetwork of GaWC's global network, but needs an empirical study based on a wide range of leading PS in the Chinese market. We explore the spatial differentiation in the connectivity of Chinese cities based on the location strategies of 323 APS firms in 287 Chinese cities. Beijing, Shanghai, Guangzhou and Shenzhen emerge as the primary nodes. The spatial distribution of banking, securities, and insurance services networks appears to be more even than those of non-financial PS firms. Regional disparity exists in terms of polycentric urban development in coastal China, as well as in the centralisation model in central and western areas. We suggest that owing to the continued tight regulation of China's state-led economy and the nature of the location strategies of 'globalised' PS firms, the urban networks created by Chinese PS firms are not only an extension of urban networks at a global scale but also an embodiment of economic activities at other scales.